Influence of cooling conditions on microstructure and mechanical property of Sn-0.3Ag-0.7Cu lead-free solder - Jattakul, Prajak; Madsa, Tavee; Sunasuan, Piyawan; Mookam, Niwat (My University, 2021)
This research has investigated the influence of cooling conditions on the microstructure and mechanical properties i.e., tensile strength and microhardness of Sn-0.3Ag-0.7Cu lead-free solder. In the experiments, casting was performed at 300°C with comparison between copper and stainless steel molds under slow and fast cooled conditions. X-ray diffractometer confirmed the presence of Cu6Sn5 and Ag3Sn phases in the solder matrix. Lead-free solder solidified under slow cooled conditions exhibited β-Sn matrix with larger grain growth as compared to the fast cooled solder. The eutectic area of intermetallic compound (IMC) was found to increase with cooling rate. The tensile strength of slow cooled solder was greater than fast cooled solder for both molds. In addition, the microhardness of the solder was also influenced by cooling rate. The dimples size of facture surface was decreased by higher cooling rate. A greater eutectic area of the Cu6Sn5 and Ag3Sn phases of initial β-Sn matrix lead to lower values of the mechanical property from fast cooled conditions.
Keywords: Cooling conditions; Mechanical property; Microstructure; Sn-0.3Ag-0.7Cu solder